2000
DOI: 10.1149/1.1393282
|View full text |Cite
|
Sign up to set email alerts
|

An Electrolyte Distribution Model in Consideration of the Electrode Wetting in the Molten Carbonate Fuel Cell

Abstract: In the molten carbonate fuel cell, the electrolyte distribution in the electrode is one of the major factors affecting cell performance. An electrolyte distribution model was developed in consideration of the electrode's wetting properties and the pore size distribution within the electrode. Because wettability data, e.g., contact angles, are required for model calculations, the meniscus heights of (Li/K)CO 3 and (Li/Na)CO 3 on Ni were measured under various anode gas conditions, and contact angles were derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 6 publications
2
39
0
Order By: Relevance
“…This was explained as related to the solubility of gas species in the electrolyte, and differences with respect to the contact angle at the three phase boundary inside the porous structure. In general, the temperature dependence of the contact angle in Li/Na electrolyte is larger (more negative) than that of Li/K electrolyte [5,7,24]. This supports the above explanation of the high temperature sensitivity of Li/Na cell performance.…”
Section: Effect Of Temperaturesupporting
confidence: 70%
“…This was explained as related to the solubility of gas species in the electrolyte, and differences with respect to the contact angle at the three phase boundary inside the porous structure. In general, the temperature dependence of the contact angle in Li/Na electrolyte is larger (more negative) than that of Li/K electrolyte [5,7,24]. This supports the above explanation of the high temperature sensitivity of Li/Na cell performance.…”
Section: Effect Of Temperaturesupporting
confidence: 70%
“…The meniscus plays an important role in controlling the reaction rate. [8][9][10][11][12][13] Inaba et al reported that the hydrogen oxidation reaction (HOR) was affected by the shape of the meniscus, which determines the diffusion path of the dissolved gas.14 With an alkaline electrolyte, interesting interfacial phenomena have been observed. [15][16][17][18][19][20][21] In a previous study, we observed an in situ meniscus motion during the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) on a platinum electrode.…”
mentioning
confidence: 99%
“…The effect of gas composition on the electrolyte distribution in the electrode is not considered in the evaluation of these experimental data, even though the electrolyte wetting properties of the Ni electrode strongly depend on gas composition. 20 The exchange current densities i 0 can be determined by solving Eq. 5, using the parameter values listed in Table IV.…”
Section: Resultsmentioning
confidence: 99%